Deconstructing the contribution of sensory cues in social approach. (24th March 2021) - Contestabile, Alessandro; Casarotto, Giulia; Girard, Benoit; Tzanoulinou, Stamatina; Bellone, Camilla
Abstract: Social interaction is a complex and highly conserved behavior that safeguards survival and reproductive success. Although considerable progress has been made regarding our understanding of same‐sex conspecific and non‐aggressive interactions, questions regarding the precise contribution of sensory cues in social approach and their specific neurobiological correlates remain open. Here, by designing a series of experiments with diverse social and object stimuli manipulations in custom‐made enclosures, we first sought to deconstruct key elements of social preference as assessed by the three‐chamber task. Our results highlight the importance of social olfactory cues in approach behavior. Subsequently, we interrogated whether a social odor would activate dopaminergic neurons of the Ventral Tegmental Area in the same way as a juvenile conspecific would. Employing in vivo recordings in freely behaving mice, we observed an increase of the firing only during the transition toward the juvenile mouse and not during the transition toward the object impregnated with social odor, suggesting that these two experiences are distinct and can be differentiated at the neuronal level. Moreover, using a four‐choice task, we further showed that mice prefer to explore complex social stimuli compared to isolated sensory cues. Our findings offer insights toward understanding how different sensory modalities contribute to the neurobiological basis of social behavior which can be essential when studying social deficits observed in autism‐, depression‐, anxiety‐, or schizophrenia‐related mouse models. Abstract : Mice preferred a juvenile conspecific and an object impregnated with social odors (Os) when respectively compared to an object. Employing in vivo recordings, we observed an increase in VTA pDA firing when experimental mice entered in the proximity of the social stimulus or the Os. On the other hand, we noticed an increase of firing only when the mice transitioned toward the juvenile, suggesting that these two perceptual experiences are distinct and can be differentiated at the neuronal level.